If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6d + -3d + 8 = 10 + 2d + -3 Reorder the terms: 8 + 6d + -3d = 10 + 2d + -3 Combine like terms: 6d + -3d = 3d 8 + 3d = 10 + 2d + -3 Reorder the terms: 8 + 3d = 10 + -3 + 2d Combine like terms: 10 + -3 = 7 8 + 3d = 7 + 2d Solving 8 + 3d = 7 + 2d Solving for variable 'd'. Move all terms containing d to the left, all other terms to the right. Add '-2d' to each side of the equation. 8 + 3d + -2d = 7 + 2d + -2d Combine like terms: 3d + -2d = 1d 8 + 1d = 7 + 2d + -2d Combine like terms: 2d + -2d = 0 8 + 1d = 7 + 0 8 + 1d = 7 Add '-8' to each side of the equation. 8 + -8 + 1d = 7 + -8 Combine like terms: 8 + -8 = 0 0 + 1d = 7 + -8 1d = 7 + -8 Combine like terms: 7 + -8 = -1 1d = -1 Divide each side by '1'. d = -1 Simplifying d = -1
| 3x-1/3=1/6 | | 13(s-7)+2=-7 | | 2y=-x*40 | | x^3+9x^2-36x=0 | | 12t+y=7 | | 16k+-17k=-9 | | 9z+2=1/2 | | 11-4=-9 | | 6-6(3X-2)=72 | | X^2+y^2+8x+4y+6=0 | | Y^2=4x-55 | | 2y=10y | | x/2-x/4=3 | | (-7)-(6*i)= | | y=7x^2+4x | | 18p-3p-10p-3=17 | | (x-45)+x+(x-45)+x+(x-45)=540 | | 4+(-3x)=8(-4x) | | 0=2cosx-2sinx | | 1.5+0.8=2.3-1.5x | | 4a+4=-(3-3a) | | 2y-5=11y+58 | | 60a-210x+155b-90x+90a= | | -9-2x=-5-8(x-1) | | 6(y+3)=72 | | 10x+7y=49 | | -29-r=3(r+1) | | Y=12x^3-12x^2-5 | | -3n+38=-5(1+3n)+7 | | 6(7+3)=72 | | 25(10)+200= | | 75(10)-300= |